1993
DOI: 10.1016/0022-0728(93)80205-v
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen reduction in an acid medium: electrocatalysis by CoNPc(1,2) impregnated on a carbon black support; effect of loading and heat treatment

Abstract: 0, reduction in an acid medium has been investigated on a transition metal macrocycle, CoNPc(l,2), impregnated on a carbon black support with a high dibutylphthalate adsorption value, using a rotating disk electrode and voltammetry techniques described previously, combined with X-ray photoelectron spectroscopy measurements. Optimal activity was found for a bilayer coverage (n = 2) at 17%-B% w/w loading. Heat treatment seems to be beneficial for n 6 3: it increases the overall number N of exchanged electrons an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…In contrast to the Fe catalysts, for the Co catalysts the ORR activity increases about as the square root of the metal content (region 0-1 wt.%). It has been proposed by some authors that the Co active site consists of two Co atoms instead of only one [42,47]. However, such a hypothesis should result in an activity increasing faster than linearly with Co content (meaning a slope >1 in a log-log plane, Fig.…”
Section: Analysis Of the Increase In Orr Activity At Low Metal Contentmentioning
confidence: 96%
“…In contrast to the Fe catalysts, for the Co catalysts the ORR activity increases about as the square root of the metal content (region 0-1 wt.%). It has been proposed by some authors that the Co active site consists of two Co atoms instead of only one [42,47]. However, such a hypothesis should result in an activity increasing faster than linearly with Co content (meaning a slope >1 in a log-log plane, Fig.…”
Section: Analysis Of the Increase In Orr Activity At Low Metal Contentmentioning
confidence: 96%
“…[15,61,62] The XRD and FT-IR results clearly showed that DAMCs derived from low-temperature pyrolysis possessed unique properties and preserved key features of the CoN4 structure, which acts as an active site for electrochemical ORR. [31][32][33][34] The Raman spectra of the as-prepared electrocatalysts showed D, G, and 2D bands without any additional variations (Figure S5, Supporting Information).…”
Section: Characterization Of Mwcnt-supported Phfcc Electrocatalystsmentioning
confidence: 99%
“…[27][28][29][30] To overcome the limitation of uncontrollable MN4 structures under high-temperature pyrolysis, processing MN4-macrocycle-based electrocatalysts at low-temperatures is a viable approach. [31][32][33][34] At low-temperatures, such as 300-600 °C, relatively moderate graphitization of the electrocatalyst system leads to sluggish electron transport behavior. This problem can be overcome using highly conductive and well-graphitized carbon materials, such as multi-walled carbon nanotubes (MWCNTs), whose delocalized sp 2 orbitals can be hybridized with highly-conjugated planar porphyrin and its analogs through strong π interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Mössbauer and X-ray absorption spectroscopy, van Veen and his collaborators proposed that the chelates metal-N 4 moiety is retained in the heat treatment, and actually binds to the carbon support [41,42,42,80,81] During the 1990's, other groups backed van Veen's hypothesis of a MeN 4 resembling site. Savy and Savinell et al prepared Fe or Co napthophthalocyanines [82][83][84] and porphyrins [85,86] with various loadings and different carbon blacks, they characterized their catalysts with Infrared (IR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and rotating disk electrode (RDE) and suggested that the Me-N 4 moiety remains intact when heat-treated up to 500 °C. The group of Dodelet, through time-of-flight secondary-ion mass spectrometry (ToF SIMS), initially proposed that the nature of the catalytic sites involved a coordination between the transition metal ion, nitrogen, and carbon support, in the form of MeN x C y + .…”
Section: Metal-free Cn X -Sitesmentioning
confidence: 99%